2005
DOI: 10.1002/elps.200406175
|View full text |Cite
|
Sign up to set email alerts
|

Sample stacking for the analysis of eight penicillin antibiotics by micellar electrokinetic capillary chromatography

Abstract: We studied the use of micellar electrokinetic capillary chromatography for separating eight penicillins. The method consists of (i) an electrophoretic separation based on micellar electrokinetic capillary chromatography, which uses sodium dodecyl sulfate (SDS) as surfactant; (ii) a sample stacking technique called reverse electrode polarity stacking mode (REPSM); and (iii) direct UV detection. The background electrolyte that gave complete separation contained 20 mM sodium borate buffer and 60 mM SDS. The sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…They include penicillins and cephalosporins (also aminocillins, carbapenems, and monobactams) (b-lactam antibiotics, http://www.cic.klte.hu/,gundat/betalaca.htm; checked on May 2005). Penicillins included in this review, ampicillin, penicillin V, penicillin G, amoxicillin, oxacillin, cloxacillin, dicloxacillin, nafcillin, and ticarcillin, have been separated using borate or phosphate-borate buffers at basic pH usually with SDS micelles [6][7][8][9][10][11][12]. As example, Fig.…”
Section: â-Lactam Antibioticsmentioning
confidence: 99%
See 3 more Smart Citations
“…They include penicillins and cephalosporins (also aminocillins, carbapenems, and monobactams) (b-lactam antibiotics, http://www.cic.klte.hu/,gundat/betalaca.htm; checked on May 2005). Penicillins included in this review, ampicillin, penicillin V, penicillin G, amoxicillin, oxacillin, cloxacillin, dicloxacillin, nafcillin, and ticarcillin, have been separated using borate or phosphate-borate buffers at basic pH usually with SDS micelles [6][7][8][9][10][11][12]. As example, Fig.…”
Section: â-Lactam Antibioticsmentioning
confidence: 99%
“…As example, Fig. 1 shows the separation of a mixture of eight of these penicillins in borate buffer at pH 8 with SDS micelles in about 20 min after an on-column sample preconcentration by stacking [8]. In addition, the use of UV-detection at low wavelengths (from 185 to 214 nm) enabled to obtain LODs ranging from 0.005 to 1.5 mg/mL (see Table 1).…”
Section: â-Lactam Antibioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also MEKC can be especially useful for the determination of penicillins from samples having high protein content (clinical samples, biological fluids), reducing the disadvantageous matrix effects caused by organic materials, while CZE through its simplicity and versatility can be successfully used for the determination of penicillins from pharmaceutical formulations (Hernandez, Borrull, Calull, 2003;Puig et al, 2005). CE methods for the specific penicillin residues determination from environmental (Bailon Perez et al, 2009) and food (Kowalski, Konieczna, 2007;Bailon Perez et al, 2009) samples were also reported lately.…”
Section: Introductionmentioning
confidence: 99%